Development of an expectation management intervention for patients with Long COVID: A focus group study with affected patients - Manuel Funk; Max Reinke; Bernd Löwe; Petra Engelmann (PLoS ONE, 2025)
Background A significant number of individuals who have contracted SARS-CoV-2 report persistent somatic symptoms after the infection has resolved. Evidence-based treatment options for Long COVID are lacking to date. To ensure that an expectation management intervention, designed for the research project SOMA.COV, addresses relevant patient needs as well as to promote treatment acceptance and adherence, a participatory approach was chosen. Objective The aim of the present study was to explore needs and wishes of patients with Long COVID regarding the preliminary version of an expectation management intervention and to thereby inform the further development of the treatment manual. Methods Twenty-two patients affected by Long COVID participated in one of four focus groups in June and July 2023. Participants were presented with the draft content of a four-session expectation management intervention. Feedback was audio-recorded, transcribed, and analyzed using thematic analysis. Results Thirteen themes relating to the main components of the intervention manual were developed. Large parts of the manual received overall positive feedback, including psychoeducation on the biopsychosocial etiology of the condition, elements of cognitive restructuring, and an imagination exercise. Patients’ response to the presented vicious circle of fear and a behavior change exercise was mixed. Modifications to the manual were made in response to patients’ feedback. Conclusion Patients with Long COVID provided positive feedback on an expectation management intervention while also highlighting important adaptations necessary for this patient group. The study results informed the finalization of the treatment manual within the SOMA.COV project, which investigates the effectiveness of this intervention for patients with Long COVID in a three-armed randomized controlled trial.